1999
DOI: 10.1093/jn/129.9.1628
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Phytochemicals Inhibit the Growth of Transplantable Human Prostate Carcinoma and Tumor Angiogenesis in Mice

Abstract: The objectives of our studies are to characterize the ability of dietary soybean components to inhibit the growth of prostate cancer in mice and alter tumor biomarkers associated with angiogenesis. Soy isoflavones (genistein or daidzein) or soy phytochemical concentrate inhibit the growth of prostate cancer cells LNCaP, DU 145 and PC-3 in vitro, but only at supraphysiologic concentrations, i.e., 50% inhibitory concentration (IC(50)) > 50 micromol/L. G2-M arrest and DNA fragmentation consistent with apoptosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
192
2
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(209 citation statements)
references
References 30 publications
12
192
2
1
Order By: Relevance
“…tamoxifen, raloxifene) have been shown to decrease circulating IGF-I levels in previous human studies [27][28][29], and may also increase some IGFBP levels [27,28]. Additionally, studies in mouse models showed a reduction of serum IGF-I or IGF-I mRNA expression in breast or prostate tissue by phytoestrogens [52][53][54]. Residual + total energy intake in linear regression model.…”
Section: Discussionmentioning
confidence: 99%
“…tamoxifen, raloxifene) have been shown to decrease circulating IGF-I levels in previous human studies [27][28][29], and may also increase some IGFBP levels [27,28]. Additionally, studies in mouse models showed a reduction of serum IGF-I or IGF-I mRNA expression in breast or prostate tissue by phytoestrogens [52][53][54]. Residual + total energy intake in linear regression model.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite similar alterations induced by pure genistein versus soy isoflavones, we consistently found that pure genistein, but not a mixture of soy isoflavones, promotes metastatic spread to lymph nodes. Genistein was found to cause antiangiogenic effects 15 and thus could cause poor oxygenation and hypoxia. Hypoxic microenvironments in solid tumors will promote alterations in gene expression and selection of tumor variants that could contribute to metastatic progression of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…15,[21][22][23][24] Feeding mice with soy phytochemical concentrate (SPC, containing genistein, daidzein and glycitein) or an aglycone isoflavone preparation reduced tumor growth of s.c. implanted human LNCaP cells in immunocompromised mice. 15,22 In a prevention study of Zhou et al, 23 using an orthotopic model of LNCaP cells in SCID mice similar to our model, SPC was more effective than genistein or soy protein. This prevention study is in agreement with the efficacy demonstrated by soy isoflavones in our therapeutic study of established prostate tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case, a protective effect of isoflavones has been observed. One study examined the role of soy and soy extracts on the growth of a transplantable prostate tumor in rats [16]. In a similar animal model, dietary genistein was also shown to inhibit prostate tumor growth [17].…”
Section: Introductionmentioning
confidence: 99%